2017
DOI: 10.1016/j.brachy.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Permanent prostate brachytherapy postimplant magnetic resonance imaging dosimetry using positive contrast magnetic resonance imaging markers

Abstract: Background/Purpose Permanent prostate brachytherapy dosimetry using CT-MRI fusion combines the anatomic detail of MRI with seed localization on CT, but requires multimodality imaging acquisition and fusion. The purpose of this study was to compare the utility of MRI only post-implant dosimetry to standard CT-MRI fusion based dosimetry. Methods Twenty-three patients undergoing permanent prostate brachytherapy with use of positive contrast MRI markers were included in this study. Dose calculation to the whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
(39 reference statements)
0
13
0
Order By: Relevance
“…One major difference compared with TRUS-planned implants evaluated on postimplant CT is the improved accuracy of prostate delineation and reproducible postimplant dosimetry. Unlike postimplant CT, which is complicated by edema (requiring a second CT at $ 30 days), we have found that differences in dosimetric coverage do not seem to be significant over time for MR-based dosimetry (1,2). Ultimately, coverage (V100 and D90) for Day 0 remained excellent and consistent with high-quality BT.…”
Section: Discussionmentioning
confidence: 67%
“…One major difference compared with TRUS-planned implants evaluated on postimplant CT is the improved accuracy of prostate delineation and reproducible postimplant dosimetry. Unlike postimplant CT, which is complicated by edema (requiring a second CT at $ 30 days), we have found that differences in dosimetric coverage do not seem to be significant over time for MR-based dosimetry (1,2). Ultimately, coverage (V100 and D90) for Day 0 remained excellent and consistent with high-quality BT.…”
Section: Discussionmentioning
confidence: 67%
“…Previous studies on MRI-only postimplant dosimetry using contrast-enhanced T1-weighted images had poor results on the detection of seeds at the boundaries of the prostate and extraprostatic seeds, therefore, were not deemed clinically reliable. 8,26 Frank et al 11 have reported excellent performance of an MRI-only workflow using C4 MR markers with the application of endorectal coil (without any loose or clumped seeds).…”
Section: Discussionmentioning
confidence: 99%
“…Also, glucagon is commonly administered to prostate patients at many clinics (including the study by Frank et al) before prostate MRI to suppress rectal movements and avoid image distortions. 11 Administration of glucagon to reduce the motion of prostate adjacent structures, including rectum, bladder, and small bowel may be considered. In addition, it is strongly recommended to scan patients with empty rectum for optimal QSM results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations